The impact of monetary policy on Islamic bank financing: bank-level evidence from Malaysia - Zulkhibri, Muhamed (2018)
Purpose. This paper aims to examine the distributional differences of Islamic bank financing responses to financing rate across bank-specific characteristics in dual banking system. The study also aims to provide understanding of how efficiently Islamic banks perform their roles as suppliers of capital for businesses and entrepreneurs. Design/methodology/approach. The study uses panel regression methodology covering all Islamic banks in Malaysia. The study estimates the benchmark model for Islamic bank financing with respect to bank characteristics and monetary policy. Findings. The evidence suggests that bank-specific characteristics are important in determining Islamic financing behaviour. The Islamic financing behaviour is consistent with conventional lending behaviour that the Islamic bank financing operates depending on the level of bank size, liquidity and capital. There is no significant difference between Islamic bank financing and conventional bank lending behaviour with respect to changes in monetary policy. Originality/value. Many problems and challenges relating to Islamic financing instruments, financial markets and regulations must be addressed and resolved. In practice, it would be a good idea if Islamic banks move away from developing debt-based instruments and concentrate more efforts to develop profit and loss sharing instruments. Doi: https://doi.org/10.1108/JEFAS-01-2018-0011